Conservation biology of Indian Mahseers - LAKRA, W S; GOSWAMI, M; SARKAR, U K (The Indian Journal of Animal Sciences, 2010)
The populations of mahseers are declining very fast in different parts of India due to indiscriminate fishing of brood stock and juveniles, fast degradation of aquatic ecosystems, construction of dams, barrages and weirs under river valley projects etc and therefore the species deserves high conservation values in India. To save this prized resource, effective conservation and propagation assisted rehabilitation strategies need to be planned and implemented in the country. This requires knowledge of genetic variation and population structure of mahseers in the wild habitat, which is yet not available comprehensively. In the present paper, an attempt has been made to review evolutionary history, present status and need of conservation of mahseer and role of conservation biology and genetics for their germplasm conservation, sustainable utilization and enhancement. We propose new ideas and suggestions, which would help saving mighty mahseers across the country.